SELF EFFICACY PELAKU BUANG AIR BESAR SEMBARANGAN DI KOTA PEKALONGAN (MODEL REKAYASA PERILAKU DAN JAMBAN TRIPIKON SEBAGAI LANGKAH PERCEPATAN PENCAPAIAN 100% ODF DI KOTA PEKALONGAN) - Nurlatif, Rr. Vita; Priharwanti, Ardiana; Maulana, Jaya (JURNAL LITBANG KOTA PEKALONGAN, 2019)
Pekalongan City targets in 2019 all villages with ODF status, so that Pekalongan City can be achieved 100% of open defecation. This strategic step must continue to be pursued, considering that as of March 2019 there were still 14 villages that had not yet reached 100% ODF, namely: Kelurahan Tirto, Pringrejo, Pasirkratonkramat, Kalibaros, Setono, Gamer, Panjang Baru, Panjang Wetan, Padukuhan Kraton, Bandengan, Krapyak, Degayu, Jenggot and Sokoduwet (Dinas Kesehatan, 2019). BABS behavior and unreachable pillars of STBM have an impact on the high increase in cases of environmental-based diseases. The results of Restu Prasetyo, et al., 2017 in the Indonesian Population journal found that 1 in 25 children under five suffer from diarrhea each year. This research method uses qualitative design with in-depth interviews with key informants and triangulation totaling 28 people consisting of village heads and BABS actors at the research locus. Data collection is done by in-depth interviews and observations. Data processing uses the stages of reduction, narrative building and pattern matching. The results of the mapping of the causes of the problem of not achieving 100% ODF at 14 loci due to 4 aspects (environment, behavior, and health services), in addition the results of the study found two approaches to the acceleration of 100% ODF through behavioral engineerin g and the application of Tripikon WC in areas with tidal conditions. Conclusion 1. The causes of BABS (defecation) in Pekalongan City are three things seen from the environmental aspect (tidal conditions, settlements close to streams or rice fields / gardens), behavior (the perpetrators are not accustomed to using the family toilet) and also services health (there is still no massive BABS stop campaign, and there is no elaboration from other agencies related to the achievement of ODF in Pekalongan City), 2. Two models are formulated, namely the behavioral engineering model and Tripikon toilet to accelerate 100% ODF in Pekalongan City. Suggestions for adopting behavioral engineering models and the application of Tripikon WC in rob affected areas require close collaboration and synergy (Government, Community, Higher Education, and Private) to implement them. Keyword: Model, behavioral engineering, tripikon toilet, ODF